Review on molecular markers for identification of Orchids - Thi Huyen Trang Vu; Thi Ly Le; Truong Khoa Nguyen; Duy Duong Tran; Hoang Dung Tran (Vietnam Journal of Science, Technology and Engineering, 2017)
Orchidaceae is one of the most valuable plant groups all over the world, and is also an impressively large and complex family of flowering plants. Effective molecular tools used for the identification of orchid species should be developed to support traditional morphological approaches. This study reviews most of the DNA fragments that have been used as taxon identifiers in researches conducted on Orchidaceae in order to assess potential molecular markers and metric measurements for the identification of orchid species.